Kepribadian Big Five untuk Melihat Perilaku Prososial Mahasiswa - Noya, Ira Novita; Dwi Putra, Achmad Irvan; Sarinah, Sarinah (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2019)
This study aims to find out the relationship between the Big Five personality and Prosocial Behavior. Major hypothesis proposed in this study is that there is a relationship between the Big Five personality and Prosocial Behavior; while the minor hypothesis is that there is a positive relationship between extraversion, agreeableness, conscientiousness and openness with prosocial behavior and there is a negative relationship between neuroticism and prosocial behavior. The subjects of this study are 127 Collegers Faculty of Economics Majoring in Accounting at Prima Indonesia University Medan and chosen by purposive sampling method. Data obtained from a scale to measure interest in the Big Five personality and Prosocial behavior. The results show the value of Anareg with F=2.901 and p=0.016 (p<0.05). Results of data analysis of minor hypothesis on the agreeableness (r=0.076, p=0.466), conscientiousness (r=0.082, p=0.420) and openness (r=0.036, p=0.735) show that there is a positive relationship between agreeableness, conscientiousness and openness with the prosocial behavior but that no significan. Results of data analysis of minor hypothesis on the neuroticism (r=0.163, p=0.099) shows that there is no negative relationship between neuroticism and the prosocial behavior. Results of data analysis of minor hypothesis on the extraversion (r =0.101, p=0.369) shows that there is no relationship between extraversion and the prosocial behavior.